Modelling AD‐relevant pathophysiology in neurons, astrocytes and microglia from two complete sets of isogenic iPSC lines generated by the ADAPTED project: Alzheimer's disease apolipoprotein pathology for treatment elucidation and development: The adapted project results. (7th December 2020) - Socorro, Alfredo Cabrera; Schmid, Benjamin; Clausen, Christian; Holst, Bjørn; Peitz, Michael; Grezella, Clara; Brustle, Oliver; Bahnassawy, Lamiaa; Bennett, Keiryn; Ried, Janina S.; Sáez, María Eugenia; Ramaswamy, Gayathri; et al.
Abstract: Background: Apolipoprotein E (APOE) genotype is the main genetic risk factor for Alzheimer's disease (AD). APOE ε2 haplotype is protective, APOE ε3 is neutral, and APOE Ɛ4 is associated with the highest risk to develop the disease. APOE highly is conserved in vertebrates, but homology between human and mouse sequence is low (73.4% for peptide and 78.7% for the genetic sequences). To better understand the contribution of each APOE allele to the pathophysiology of AD it is necessary to generate preclinical models that recapitulate the molecular and biochemical properties of this complex gene. Within ADAPTED (Alzheimer's Disease Apolipoprotein Pathology for Treatment Elucidation and Development) project we have generated and characterized human iPSC‐derived brain cells to fill this important gap. Method: All ADAPTED isogenic iPSC‐lines were differentiated into clinically relevant cell types (neurons, astrocytes and microglia) that were characterized using unbiased methodologies (transcriptomics, metabolomics and proteomics) and functional assays such as neuronal activity, cytokine release and phagocytosis. We performed all possible comparisons across genotypes, and mostly focused on results that were replicated across the two sets. Result: We prioritized the study of iPSC‐derived glial cells based on expression levels of apoE and their critical role in brain function and AD pathophysiology. Our strategy led to the identification of APOE allele‐specific molecular signatures and pathways that partially replicates clinical findings (e.g. inflammatory response and metabolic properties). Functional assays revealed genotype differences that were also replicated in different genetic backgrounds. Conclusion: Systematic comparison of relevant cells types stratified by APOE genotypes revealed key signatures and mechanisms that have been associated to AD. Data generated from iPSC‐derived cells proves this model as a reliable tool to further study the human biology of APOE, providing one step further in our understanding of AD and the potential identification of more effective therapies. iPSC lines generated within ADAPTED are globally available to the scientific community via EBiSC repository.